As interfaces entre cooperativismo e economia solidária - Reni Luiz Stahl (Universidade do Vale do Rio dos Sinos (UNISINOS), 2013)
Solidarity Economy has been defended in many works as an alternative to the severe condi- tions of precariousness in labour relations. For Singer (2002, 2003), one of the promoters of the aforementioned project, Popular Solidarity Economy, as it is also recognized, can be considered an innovative production method within the capitalist system. His main argument is that such methods, even occupying the “loopholes” of the system, could move towards a new social organization of socialist slant, through its multiplication. Based on principles that were raised with the first cooperative in Europe 186 years ago with the first consumer cooperative created by William King or 169 years ago since the emergence of the Rochdale Pioneer Cooperative, we can observe how updated Solidarity Economy is. It is worth mentioning the principle of democratic management, which was implemented by cooperative workers, who did it in a bold and innovative way within the innovative environment in Europe then, when there was no experience of exercise in power on the basis of “one person, one vote” in the European political scene then. This innovative form of business organization was part of the environment of struggles of workers, as in processes of formation of cooperative factories or recovery of bankrupt factories, but also in other forms of claims and associativism. Many of these worker initiatives, then and even today, were eventually grouped and mixed with other forms of organization, promotion, and public policies that seek solutions in for mitigating structural problems such as unemployment and social exclusion. Thus, forces of resistance or revolutionary movements of civil society organizations, welfare practices, mutualism, cooperativism and solidarity became eventually parts of the same project of Solidarity Economy.